2016
DOI: 10.1103/physrevb.93.195115
|View full text |Cite
|
Sign up to set email alerts
|

Many-body effects on Cr(001) surfaces: An LDA+DMFT study

Abstract: The electronic structure of the Cr(001) surface with its sharp resonance at the Fermi level is a subject of controversial debate of many experimental and theoretical works. To date, it is unclear whether the origin of this resonance is an orbital Kondo or an electron-phonon coupling effect. We have combined ab initio density functional calculations with dynamical mean-field simulations to calculate the orbitally resolved spectral function of the Cr(001) surface. The calculated orbital character and shape of th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 32 publications
2
10
0
Order By: Relevance
“…These systems allow for a direct experimental manipulation of the Kondo scale and offer a rich playground for the exploration of connections between theoretical models and real-world physics. Section 4.3 is instead devoted to the study on the Cr(001) surface [86], which has been raising a long debate on the many-body nature of its low-energy spectral features. We reveal that the spectral feature observed close to the Fermi level is a consequence of changes in the electronic structure at the surface, as well as complex many-body effects in certain orbitals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These systems allow for a direct experimental manipulation of the Kondo scale and offer a rich playground for the exploration of connections between theoretical models and real-world physics. Section 4.3 is instead devoted to the study on the Cr(001) surface [86], which has been raising a long debate on the many-body nature of its low-energy spectral features. We reveal that the spectral feature observed close to the Fermi level is a consequence of changes in the electronic structure at the surface, as well as complex many-body effects in certain orbitals.…”
Section: Discussionmentioning
confidence: 99%
“…The origin of the peak was so far discussed either to be of single particle nature (surface state, [85]) or of many-body nature (orbital Kondo effect [84]). Here, we review our work from reference [86] where we use the LDA+DMFT method to unravel the nature of the resonance in the electronic spectrum of Cr(001). We show that local electronic correlations play a key role for understanding the electronic structure of Cr(001).…”
Section: Electronic Structure Of the Cr(001) Surfacementioning
confidence: 99%
“…40 In order to use the CTQMC results as a benchmark the Cr(001) surface is modelled in exactly the same way as in Ref. 16. This is a slab of 10 atomic layers with a vacuum of approximately 16 Å stacked in the z-direction and perdiodically continued in the x and y direction.…”
Section: Computational Detailsmentioning
confidence: 99%
“…These newest experiments hint in the direction of a many-body interpretation of the resonance. Also recent dynamical mean-field theory (DMFT) calculations within the continuous-time quantum Monte Carlo (CTQMC) solver hint in this direction 16 . Namely it was 2 observed that the resonance was very robust against artificial shifts in the one-particle energies of the d xz , d yz and d z 2 states, which points towards a dominant many-body contribution.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation